HARMONISASI PENGATURAN TINDAK PIDANA KHUSUS YANG OBJEKNYA TULISAN DAN BERITA YANG ISINYA PALSU - Ferdian, Ardi (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2016)
Harmonization of Legislation is a process that is geared towards harmony between the Act by Act other so that there is no overlap, inconsistencies, conflicts or disputes in the regulation. In Act 10 of 2004 on the Establishment of legislation there are signs which point to the importance of harmonization Legislation regulation. Article 5 of Law No.10 of 2004 on the Establishment of legislation determine rugulation Legislation is considered good if it fulfills the principle of legislation that either include clarity of purpose, the correspondence between the type and substance, can be implemented, usefulness, and clarity of the formulation. Special Crimes About Writing And News The contents Counterfeit actions are criminal acts, deliver news and use writing false contents. In this criminal act contains elements of the writing or the news to false, although the object of criminal acts themselves are not always about writing or false news. The author found some law governing the Special Crimes About Writing And News All contents are false, namely Article 57 jo 36 paragraph (5) letter a Law No.32 of 2002 on Broadcasting, Article 28 of Law No.11 of 2008 on ITE, Article 86 of Law No.23 of 2002 on the Protection of the Child, Article 19 of Law No.21 of 2007 on the Eradication of Trafficking, Article 69 and Article 70 of Law No.20 of 2003 on National Education System, Article 55 of Law No.14 of 2008 concerning Public, and that the last of Article 9, Article 22, and Article 23 of Law No.31 of 1999 on Corruption Eradication was changed by Act No.20 of 2001.